2021
DOI: 10.1002/chem.202101592
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Fibrillation Pathway of α‐Synuclein by Interaction with Antimicrobial Peptide LL‐III

Abstract: Liquid‐liquid phase separation (LLPS) has emerged as a key mechanism for intracellular organization, and many recent studies have provided important insights into the role of LLPS in cell biology. There is also evidence that LLPS is associated with a variety of medical conditions, including neurodegenerative disorders. Pathological aggregation of α‐synuclein, which is causally linked to Parkinson's disease, can proceed via droplet condensation, which then gradually transitions to the amyloid state. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Actually, a few recent studies have reported that the LLPS of amyloid proteins could be regulated by small molecules or peptides, which further affect its amyloid aggregation. For example, LL‐III, a kind of antimicrobial peptide extracted from the venom of the eusocial bee, was reported to stabilize α‐Syn droplets and prevent the conversion of α‐Syn to the fibrillar state [60] . Another study reported that C 1 , a synthetic derivative of curcumin, could reduce the size and number of the Tau protein droplets to inhibit Tau protein‘s amyloid aggregation strongly [61] .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, a few recent studies have reported that the LLPS of amyloid proteins could be regulated by small molecules or peptides, which further affect its amyloid aggregation. For example, LL‐III, a kind of antimicrobial peptide extracted from the venom of the eusocial bee, was reported to stabilize α‐Syn droplets and prevent the conversion of α‐Syn to the fibrillar state [60] . Another study reported that C 1 , a synthetic derivative of curcumin, could reduce the size and number of the Tau protein droplets to inhibit Tau protein‘s amyloid aggregation strongly [61] .…”
Section: Discussionmentioning
confidence: 99%
“…These receptors may have less affinity to the α-Syn conformers formed in the presence of Zn 2+ compared to the other types of fibrils used in the current study. Alternatively, polymorphically different fibrils could have different seeding activities once entered the cells 36 . According to our unpublished data, the polymorphically different fibrils formed in the presence of various cations can imprint their morphology in the newly formed fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…This along with the fact that there are a number of receptors at the cell membrane, which bind to β-sheet rich conformers such as cellular prion protein 36 , led us to the hypothesis that maybe there are speci c receptors at the cell surface for particular types of α-Syn oligomers, whose activation upon binding of the oligomers can transduce various deadly or survival intracellular cell signals. Alternatively, polymorphically different brils could have different seeding activities once entered the cells 37 . Therefore, the authors suggest that the type of β-sheet formed in brils can affect the interactions of brils with the potential receptors at the cell surface and consequently their cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%